VISUALIZING EDUCATIONAL INFORMATION: PRIMARY SCHOOL TEACHERS’ VIEWS - Topuzov, Oleh; Malykhin, Oleksandr; Aristova, Nataliia; Zahorulko, Maryna; Lipchevska, Inna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
The study’s major purpose was to compare primary school teachers’ views on visualizing educational information under conditions of the reform of Ukrainian education being in progress and unforeseen global impacts (martial law in Ukraine and the Covid-19 pandemic). The survey was conducted within the time period of 2019 spring – 2022/2023 winter. The total number of respondents consisted of 265 primary school teachers. Gradual primary school teachers’ reorientations regarding the essence of visualizing educational information were determined as a strong positive tendency: from the position of its identification associated with the didactic field of the use of visual means to the consideration of visualizing educational information as an effective didactic tool boosting the use of interactive methods of teaching and learning in primary school. A significant rethinking of the didactic potential of using visualization in the educational process of primary school was being observed. The implementation speed of forms, methods and means of information visualization in the educational process of primary school changed positively as a result of experimental didactic influences. But the dynamics of changes was not correspondingly enough to the needs of modern educational requirements. Concluded the inappropriate development of primary school teachers’ visualizing educational information skills that are to be intensively improved among primary school teachers.